Mixed-flow pumps modeling, simulation, and measurements - Li, Wei; Ji, Leilei; Agarwal, Ramesh K. 1947-; Shi, Weidong; Zhou, Ling (Wiley, 2024)
Mixed-flow PumpsModeling, Simulation, and MeasurementsLearn to improve and optimize the design and operation of mixed-flow pumpsMixed-flow pumps have a huge range of applications in agriculture, hydroelectric power, and other industries that incorporate fluid transport. They are centrifugal pumps incorporating the characteristics of both axial and radial pumps to increase the flow rate and discharge pressure. Though essential in a variety of industries, they pose serious challenges to numerical simulation methods, challenges which are starting to be met by the application of computational fluid dynamics using high-performance computing.Mixed-flow Pumps introduces engineers and researchers to this subject and its important applications. Incorporating all major varieties of mixed-flow pumps used in industrial applications, it employs methods from advanced computational fluid dynamics and high-precision flow field experimentation to characterize and analyze these crucial technologies. Moving from the fundamentals of the technology to its most advanced applications, it's an essential resource for engineers and industry practitioners looking to develop their understanding of fluid transport.Mixed-flow Pumps readers will also find:* Detailed information on how to design and optimize mixed-flow pumps to meet the increasingly stringent industry demands* Detailed information on energy performance tests and experiments, methods for data analysis, entropy production theory, CFD solutions using Reynolds-Averaged Navier-Stokes (RANS) equations, and more* An authoritative team with immense global experience in flow pumps and broader industrial experienceMixed-flow Pumps is a useful reference for mixed-flow pump design by academic researchers, including graduate students, industry practitioners, and test engineers
Preface; Acknowledgements; List of Acronyms; List of Symbols; 1. Introduction; 2. Basic Concepts and Theory of Mixed-Flow Pumps; 3. CFD As A Flow Simulation Tool; 4. Analysis Methods; 5. Experimental Methods, Data and Analysis; 6. Application of Turbulence Models in Mixed-flow Pump; 7. Tip Leakage Flow in a Mixed-Flow Pump; 8. Rotation Stall in a Mixed-Flow Pump; 9. Passive Suppression of Rotating Stall in Mixed-Flow Pump; 10. Cavitation in a Mixed-Flow Pump; 11. Vortex Dynamics Characteristics in the Tip Region Using Wray-Agarwal Turbulence Model; 12. Multiphase Flow Simulations of Sediment Particles in Mixed Flow Pumps; Index
Keywords: Maschinenbau, Fertigungstechnik